Immune cell infiltration and the genes associated with ligamentum flavum hypertrophy: Identification and validation - Duan, Yang; Ni, Songjia; Zhao, Kai; Qian, Jing; Hu, Xinyue (Frontiers in Cell and Developmental Biology, 2022)
Ligamentum flavum hypertrophy (LFH) is a common cause of spinal stenosis. The aim of the current study was to identify the differentially expressed genes (DEGs) in LFH and the molecular mechanisms underlying the development of and immune responses to LFH. The gene expression omnibus (GEO) database was used to obtain the GSE113212 dataset, and the DEGs were derived from microarray data. To identify critical genes and signaling pathways, gene ontology enrichment, Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, and protein-protein interaction (PPI) network analyses were performed, followed by immune cell infiltration and Friends analyses using the retrieved datasets. The results were validated using quantitative real-time PCR. The 1530 DEGs identified comprised 971 upregulated and 559 downregulated genes. KEGG analysis revealed that DEGs were mostly enriched in the PI3K-Akt signaling pathway, while PPI network analysis identified tumor necrosis factor, interleukin (IL)-6, IL-10, epidermal growth factor receptor, and leptin as important nodes, which was validated by qPCR and IHC in human LFH tissues in vitro. A significant positive correlation was found between key LFH immune-related DEGs and several immune cell types, including T and B cells. The findings of the present study might lead to novel therapeutic targets and clinical approaches, as they provide insights into the molecular mechanisms of LFH.